Avascular necrosis under different treatment in children with developmental dysplasia of the hip: a network meta-analysis. Issue 4 (8th November 2021) - Qiu, Meiling; Chen, Meiyi; Sun, Hao; Li, Deng; Cai, Zhiqing; Zhang, Wenhui; Xu, Jie; Ma, Ruofan
Abstract : The objective of this study was to evaluate the incidence of avascular necrosis (AVN) of the femoral head in children less than 3 years of age with developmental dysplasia of the hip (DDH) treated with closed reduction, open reduction alone and open reduction combined with osteotomy. We reviewed clinical trials from the PubMed, EMBASE and Cochrane Library databases (up to November 2020) that were related to closed reduction, open reduction alone and open reduction combined with osteotomy for the treatment of children under 3 years of age with DDH. The screening and quality evaluation of the literature were performed independently by two researchers. In case of disagreement, a third researcher resolved the discourse. Finally, the data were extracted, and the R software and GeMTC program package were used to conduct a network meta-analysis (NMA). The evaluation index was the incidence of AVN. Fourteen articles were included. The NMA showed that in terms of the incidence of AVN, cases treated with open reduction alone were higher than those with closed reduction, and the difference was statistically significant. Open reduction alone had the highest probability (94.4%) of having the highest incidence of AVN, followed by open reduction combined with osteotomy (5.5%) and closed reduction (0.1%). In the treatment of children with DDH who are younger than 3 years old, open reduction alone is most likely to be the treatment with the highest incidence of AVN, followed by open reduction combined with osteotomy. The closed reduction had the smallest probability of AVN.